The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1049/gtd2.12430
|View full text |Cite
|
Sign up to set email alerts
|

An overview of stability challenges for power‐electronic‐dominated power systems: The grid‐forming approach

Abstract: Inverter-based generators (IBGs) are becoming popular in modern power systems. When the penetration of IBGs is increasing in power systems, new stability, protection, and monitoring challenges are introduced in the grid. Grid-forming (GFM) control of converters is seen as a promising solution for future power grids to overcome particular stability challenges. Here, the technical challenges of the GFM-based IBGs are reviewed from the point of view of TSOs and academic research. The properties of different GFM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…It has been also observed that the issues related to power-frequency oscillations can affect both the local and inter-area modes of the system. Proper assessment of the control strategy of the non-synchronous generation sources is therefore necessary from an overall systemic point of view, especially when a grid-forming control is implemented [4]. In this case, the damping characteristics of the chosen control strategy must be verified and enhanced with available solutions, if necessary, and control schemes that are capable of providing a positive contribution to the oscillatory characteristics of the power system should be preferred.…”
Section: Case Study: the Colombian Interconnected National Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been also observed that the issues related to power-frequency oscillations can affect both the local and inter-area modes of the system. Proper assessment of the control strategy of the non-synchronous generation sources is therefore necessary from an overall systemic point of view, especially when a grid-forming control is implemented [4]. In this case, the damping characteristics of the chosen control strategy must be verified and enhanced with available solutions, if necessary, and control schemes that are capable of providing a positive contribution to the oscillatory characteristics of the power system should be preferred.…”
Section: Case Study: the Colombian Interconnected National Systemmentioning
confidence: 99%
“…These two control concepts and the related stability challenges have been studied in several works [3][4][5][6][7][8][9][10][11][12][13][14]. The work in [3] stresses that the controller settings of converter-based resources significantly impact the stability properties of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the energy uncertainty problem in IES has been actively studied in various literature. Depending on the uncertainty modelling approach, these studies can be divided into two types: (1) the deterministic models based on operating or contingency reserve requirements [11]; (2) the non-deterministic models based on stochastic [12] or robust optimization [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the waste heat flue gas can be recycled by waste heat boilers. Its mathematical model is shown in (1).…”
Section: Gas Turbine Gtmentioning
confidence: 99%